Epidemiology of Typhoid Fever in Iran during Last Five Decades from 1962-2011 - Hossein Masoumi Asl; Mohammad Mehdi Gouya; Mahmood Nabavi; Nooshin Aghili (Tehran University of Medical Sciences, 2013)
Background: Typhoid fever is one of the most important infectious diseases transmitted by contaminated food and water. This study aimed at epidemiological features of disease during the last five decades, over the period from 1962-2011.Methods: A retrospective cross-sectional study was conducted using typhoid fever national surveillance data.Results: The highest incidence of typhoid fever was registered in 1965 with 133.4 /100,000 cases/year and the lowest in 2011 with 0.52/100,000 cases/year. Typhoid fever incidence in Iran had three phases. Before the year 1969, with high incidence >100 (phase 1), the period between1969-1996 with medium (10-100), (Phase 2) and the phase 3 has inaugurated from 1996 until now with low incidence rate less than 10 /100,000. Kermanshah Province was the most infected area. Most cases were occurred in warm months in 2010. Of 196 (31%) cases were under 15 years old whom were more affected. 53.6% of total cases in 2010 were female and 56.6% stayed in rural area. In 2010, 27.8% cases were confirmed. Among positive cases, the sources of culture were 46.8% stool, 37.2% blood, 14.6% urine and 1.2% bone marrow. Following treatment, 97.8% of cases were recovered completely and in 1.6% of cases had experienced complications and only 0.6% of confirmed cases have been died.Conclusion: As a result of development in socio-economic condition in Iran, the typhoid fever incidence has been dramatically declined from high (133.4/100,000 cases/year) in 1965 to low (0.52/100,000 cases/year) in 2011.